TREATMENT OF TEXTILE EFFLUENTS BY LOW COST AGRICULTURAL WASTES: BATCH BIOSORPTION STUDY - H. N. Bhatti; S. Sadaf; A. Aleem (Journal of Animal and Plant Sciences, 2015)
The present investigation deals with the treatment of different dye containing effluents by using different agricultural waste biomasses (corncobs, sugarcane bagasse, cotton sticks, sunflower and peanut husk). Samples of textile wastewater were collected from five different textile industries of Faisalabad, Pakistan. Screening test was conducted to select the biosorbent with maximum dye removal efficiency for each of textile wastewater samples. Different process parameters like biosorbent dose, shaking speed and temperature were optimized during the study. The biosorption process using corncobs biomass was found to be good for the removal of dyes up to 79% from the one real textile wastewater sample. The biosorption efficiency of adsorbents was maximum at 0.3 g 50mL-1 of adsorbent dose with 120 rpm shaking speed and 303 K temperature. Thermodynamic study was also carried out to evaluate different parameters like free energy change (ΔG°), enthalpy change (ΔH°) and entropy change (ΔS°) and biosorption process was found to be exothermic. Characterization of effluents was carried out before and after the biosorption process to check out the effect of process on the removal of Chemical Oxygen Demand (COD), Total Dissolved Solids (TDS) and Total Suspended Solids (TSS). The results proved that agricultural wastes are good option for the removal of color and COD from real textile effluents.
Keywords: Agricultural wastes; COD; Color; TDS; Thermodynamic study; Biosorption